Online health & beauty web site / Salwa Faharudin - Salwa , Faharudin (2003)
V-Nuz.com is a Health & Beauty On-line System, mainly focus on women's needs. This system is approach d because Health & Beauty supplies are information-intensive products, mostly nonperishable, easy and cheap to ship, and generate lots of repeat purchases. The main focus of this system is to create awareness regarding women health and provide substantial information on women lifestyle today's. This system include online transaction such as search capabilities, product catalog user registration and administrator site.The main challenge of this project is to develop an online system that will be information as well as attractive enough to set it apart from the current web sites on the Internet. V-Nuz.com is developed with a combination of web programming technologies namely Active Server Page, Vb Script, HTML and JavaScript. The entire platform for V-Nuz.com require Windows 9x machine and Microsoft Internet Explorer 4.0 above.